2006
DOI: 10.1007/s11231-006-9019-1
|View full text |Cite
|
Sign up to set email alerts
|

Forced migration, adolescence, and identity formation

Abstract: Adolescence is a complex biopsychosocial phenomenon. All the inner-subjective changes in adolescents take place within the context of a specific social environment, which offers the necessary ideological setting that adolescents must confront in the course of their identity formation. Forced migration creates conditions under which the adolescent Ego may be traumatized more easily, resulting in the development of defensive mechanisms, which may interfere with the natural process of identity formation. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
10
0
4
Order By: Relevance
“…One of the values of this study is its extension over 20 years with separate assessment periods of equal length that involved two subsequent classification systems, particularly because some of the diagnostic criteria changed during the transition from ICD-9 to ICD-10. In addition, both the sample size and the proportion of patients with a migration background in this study are considerably larger than those in previous studies (18, 20, 21, 38). A further advantage is that the effects of SES were controlled for, supporting previous studies in adults that suggested that differences in SES should be considered a crucial risk factor for specific mental health problems (39), particularly for psychotic disorders (40) and depression (41).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…One of the values of this study is its extension over 20 years with separate assessment periods of equal length that involved two subsequent classification systems, particularly because some of the diagnostic criteria changed during the transition from ICD-9 to ICD-10. In addition, both the sample size and the proportion of patients with a migration background in this study are considerably larger than those in previous studies (18, 20, 21, 38). A further advantage is that the effects of SES were controlled for, supporting previous studies in adults that suggested that differences in SES should be considered a crucial risk factor for specific mental health problems (39), particularly for psychotic disorders (40) and depression (41).…”
Section: Discussionmentioning
confidence: 68%
“…It is not uncommon for migrants to experience discrimination, work- or school-related stressors and improved or worsened access to health care services. In particular, children and adolescents can be greatly affected by the migration process (17, 18). However, the variety of experiences and the reasons for migration indicate that not all children and adolescents with a migration background face similar experiences before or after migration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other participants struggled to overcome the conditions of oppression, internalising negatively the perceptions from the dominant culture as a reflection of the self. Anagnostopoulos et al (2006) investigated how a traumatic situation, such as forced migration, may affect the process of identity formation in adolescence. Using a case study approach, the study examined the experiences of two adolescent males who were forced to immigrate to Greece where they were faced with further marginalisation as a part of a minority ethnic group.…”
Section: Socio-environmentalmentioning
confidence: 99%
“…Arrangierte Heiraten und forcierte Migration [2] oder Ehrenmorde, in westlichen Ländern unter Strafe gestellt, können häufig als Spitze eines Eisberges von tiefgreifenden Konflikten der Akkulturation verstanden werden. Therapien stoßen hier leider oft an Grenzen [5].…”
Section: Bedeutung Der Akkulturation In Der Transkulturellen Psychothunclassified